Durability Assessment of Sustainable Mortar by Incorporating the Combination of Solid Wastes: An Experimental Study - Mohammad Nadeem Akhtar; Dima A. Husein Malkawi; Khaldoon A. Bani-Hani; Abdallah I. Husein Malkawi (Civil Engineering Journal, 2023)
The excessive mining of high-quality river sand for cement sand mortar resulted in environmental impacts and ecological imbalances. The present study aims to produce sustainable mortar by combining solid waste such as desert sand, stone dust, and crumb rubber to fully replace river sand. In addition, replacing cement with silica fume helps reduce the environmental carbon footprint. The present research prepared three types of mortar mixes: natural dune sand mortar (M1), natural dune sand stone dust crumb rubber mortar (M2), and natural dune sand stone dust crumb rubber silica fume mortar (M3). The developed mortar samples were examined at ambient and elevated temperatures of 100°C, 200°C, and 300°C for 120 minutes. Furthermore, 3 cycles of 12 hours each at freezing temperature (-10° ± 2°C) and crushed ice cooling (0° to -5°C) were also tested. Results of the study showed an increment in compressive strength values in M1, M2, and M3 mortar mixes (up to 200°C). Later, an abrupt drop in the compressive strength was noticed at 300°C in all mixes M1, M2, and M3, respectively. The mix M3 combinations resist heating impacts and perform significantly better than other mixes M1 and M2. Also, M3 combinations resist the cooling effect better than M1 and M2. It can be concluded that the mortar mix M3 with desert sand, stone dust, crumb rubber, and silica fume combination is considered the best mix for both heating and cooling resistance. Hence, the developed sustainable mortar M3 combination can be utilized in all adverse weather conditions. Doi: 10.28991/CEJ-2023-09-11-09 Full Text: PDF